Protein analysis and purification : - Rosenberg, Ian M. (Birkhäuser, 2005)
This second edition pays homage to the computer explosion and the various genome projects that have revolutionized how benchtop scienti?c research is performed. Bioinformatics and In silico science are here to stay. However, the second edition still includes recipes for preparing buffers and methods for lysing cells.